Making money the smart way guide to investing in shares and real estate - Prince, Jimmy B (McGraw-Hill, 2000)
Exploring the many options available to the personal investor, this book explains how 'to make money the smart way' by focusing on two of the most popular and user-friendly options: real estate and shares. He looks into almost every aspect relevant to the investor, from establishing a share portfolio to property trusts and the tax implications.